The effectiveness of HRIS by using Technology Acceptance Model ( TAM ) on human resources perfomance at Wisma Persekutuan / Wan Siti Sarah Nabilah Wan Muhd Kamil - Wan Muhd Kamil, Wan Siti Sarah Nabilah (Faculty of Business and Management, 2013)
The purpose of this study is to measure HRIS effectiveness by using TAM model and how it impacts on Human Resources (HR) performance. Scope of this study is focus on respondents. The respondents of this research are employee at Human Resources Department in Federal and focused on HR executives and HR staff. This is because; both of these respondents are those who deal daily with HRIS. It is important to get their view and opinion regarding impact on using HRIS in performing their jobs. In addition, it also can focus on questionnaire. Selt:rated questionnaire will be used as a method of gathering data and it will distribute manually to the HR staff. Besides that, scope that can be focus is work environment such as the effectiveness and efficiency of BRJS could influence the ways employee feelings and will affect the entire results of this research. Methods that been use in this research are research design, sampling frame, population, sampling technique, sample size, unit analysis, data collection procedures, instrument, validity of instrument and reabi lity. Findings of this researcher is use to analyze the actual data by using descriptive statistic which Correlation analysis was conducted in order to measure how variables or rank orders are related. Table below was presented the relationship between effectiveness of HRIS by Using Technology Acceptance Model (TAM) on human resources performance at Wisma Persekutuan Ayer Keroh, Melaka. The correlations between the Technology Acceptance Model (TAM) in elements of perceives ease of use and perceives usefu lness of HRIS with human resource process, time and cost saving, decision making and information effects were interpreted as Correlation analysis is a tenn that refers to the strength of a relationship between two variables. As a conclusion, the application of HRIS system must used in higher education institutions provide the utmost update ability use of resources, speed, compatibility, updateability, accessibility, data integrity,privacy and security.